Emerging Trends in STEAM Education: Advancing 5C Skills for Future-Ready Learners - Febriawati, Rizqiana Nur; Adhim, Fauzan; Hariyanto; Pradana, Pascalian Hadi (Indonesian Journal of Educational Research and Review, 2024)
Observations reveal several issues in education, including reliance on conventional teaching methods, educators' preference for competitive and individualistic approaches over collaborative ones, and limited opportunities for students to develop communication skills. This review aims to explore the importance of implementing the STEAM learning model, the underlying causes of educational challenges, and strategies to enhance students' 5C skills. The study adopts a Systematic Literature Review approach using the PRISMA method. Articles were retrieved from the Scopus database with the assistance of the Publish or Perish application. A total of 14 relevant and eligible articles were critically reviewed and analyzed to meet the research objectives. The findings demonstrate that the STEAM learning model is an innovative educational approach that effectively instils 5C skills—critical thinking, creativity, collaboration, communication, and confidence—in students. The integration of STEAM with other learning models provides students with relevant and practical learning experiences to address diverse educational needs. Implementing STEAM prepares future generations to face global challenges with comprehensive and relevant skill sets.